Population Pharmacokinetics and Pharmacodynamics of Doripenem in Obese, Hospitalized Patients. (March 2017) - Chung, Eun Kyoung; Fleming, Megan R.; Cheatham, S. Christian; Kays, Michael B.
Background: Doripenem population pharmacokinetics and dosing recommendations are limited in obesity.Objective: To evaluate the population pharmacokinetics and pharmacodynamics of doripenem in obese patients.Methods: Hospitalized adults with a body mass index (BMI) ≥ 40 kg/m 2 or total body weight (TBW) ≥45.5 kg over their ideal body weight received doripenem 500 mg every 8 hours, infused over 1 hour. Population pharmacokinetic analyses were performed using NONMEM, and Monte Carlo simulations were performed for 5 intermittent and prolonged infusion dosing regimens to calculate probability of target attainment (PTA) at 40% and 100% f T>MIC (free drug concentrations above the minimum inhibitory concentration).Results: A total of 20 patients were studied: 10 in an intensive care unit (ICU) and 10 in a non-ICU. A 2-compartment model with first-order elimination best described the serum concentration-time data. Doripenem clearance (CL) was significantly associated with creatinine CL (CRCL), volume of the central compartment with TBW and ICU residence, and volume of the peripheral compartment with TBW ( P < 0.05). Using 40% f T>MIC, PTA was >90% for all simulated dosing regimens at MICs ≤2 mg/L. Using 100% f T>MIC, prolonged infusions of 1 g every 6 hours and 2 g every 8 hours achieved >90% PTA at MICs ≤2 mg/L.Conclusions: CRCL, ICU residence, and TBW are significantly associated with doripenem pharmacokinetics. Currently approved dosing regimens provide adequate pharmacodynamic exposures at 40% f T>MIC for susceptible bacteria in obese patients. However, prolonged infusions of larger doses are needed if a higher pharmacodynamic target is desired.